Highly sensitive and specific detection of hepatitis B virus DNA and drug resistance mutations utilizing the PCR-based CRISPR-Cas13a system. (March 2021) - Wang, S.; Li, H.; Kou, Z.; Ren, F.; Jin, Y.; Yang, L.; Dong, X.; Yang, M.; Zhao, J.; Liu, H.; Dong, N.; Jia, L.; et al.
Abstract: Objectives: Undetectable or low-level hepatitis B virus (HBV) DNA and drug resistance mutations in patients may increase the risk of HBV transmission or cause active viral replication and other clinical problems. Here, we established a highly sensitive and practical method for HBV and drug resistance detection using a polymerase chain reaction (PCR) -based CRISPR-Cas13a detection system (referred to as PCR-CRISPR) and evaluated its detection capability using clinical samples. Methods: Specific CRISPR RNAs (crRNAs) are designed for HBV DNA detection and YMDD (tyrosine-methionine-aspartate-aspartate) variant identification. The HBV DNA was detected in 312 serum samples for HBV diagnosis using quantification PCR (qPCR) and PCR-CRISPR. Additionally, 424 serum samples for YMDD testing were detected by qPCR, direct sequencing, and our assay. Results: Using PCR-CRISPR, one copy per test of HBV DNA was detected with HBV-1 crRNA in 15 min after PCR amplification. Consistent results with qPCR were observed for 302 samples, while the remaining 10 samples with low-level HBV DNA were detectable by PCR-CRISPR and droplet digital PCR but not by qPCR. PCR-CRISPR diagnosed all 412 drug-resistant samples detected by the YMDD detection qPCR kit and direct sequencing, as well as the other 12 drug-resistant samples with low-level HBV DNA undetectable by qPCR and direct sequencing. Conclusions: We developed a novel PCR-CRISPR method for highly sensitive and specific detection of HBV DNA and drug resistance mutations. One copy per test for HBV DNA and YMDD drug resistance mutations could be detected. This method has wide application prospects for the early detection of HBV infection, drug resistance monitoring and treatment guidance. Graphical abstract: Image 1